Clinical features and severe acute respiratory syndrome-coronavirus-2 structural protein-based serology of Mexican children and adolescents with coronavirus disease 2019. - Karen Cortés-Sarabia; Armando Cruz-Rangel; Alejandro Flores-Alanis; Marcela Salazar-García; Samuel Jiménez-García; Griselda Rodríguez-Martínez; Juan Pablo Reyes-Grajeda; Rosa Isela Rodríguez-Téllez; Genaro Patiño-López; Israel Parra-Ortega; Oscar Del Moral-Hernández; Berenice Illades-Aguiar; et al. (PLoS ONE, 2022)
Severe acute respiratory syndrome (SARS)-coronavirus (CoV)-2 infection in children and adolescents primarily causes mild or asymptomatic coronavirus disease 2019 (COVID-19), and severe illness is mainly associated with comorbidities. However, the worldwide prevalence of COVID-19 in this population is only 1%-2%. In Mexico, the prevalence of COVID-19 in children has increased to 10%. As serology-based studies are scarce, we analyzed the clinical features and serological response (SARS-CoV-2 structural proteins) of children and adolescents who visited the Hospital Infantil de México Federico Gómez (October 2020-March 2021). The majority were 9-year-old children without comorbidities who were treated as outpatients and had mild-to-moderate illness. Children aged 6-10 years and adolescents aged 11-15 years had the maximum number of symptoms, including those with obesity. Nevertheless, children with comorbidities such as immunosuppression, leukemia, and obesity exhibited the lowest antibody response, whereas those aged 1-5 years with heart disease had the highest levels of antibodies. The SARS-CoV-2 spike receptor-binding domain-localized peptides and M and E proteins had the best antibody response. In conclusion, Mexican children and adolescents with COVID-19 represent a heterogeneous population, and comorbidities play an important role in the antibody response against SARS-CoV-2 infection.